1973
DOI: 10.1172/jci107239
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Bile Canalicular Enzymes in Cholestasis. A POSSIBLE CAUSE OF BILE SECRETORY FAILURE

Abstract: A B S T R A C T Bile secretory failure (cholestasis) may result from several possible mechanisms involved in bile secretion. We have examined the possibility that abnormalities in enzyme content, composition, and turnover of liver plasma membrane constituents are altered in cholestasis.Severe and mild cholestasis were produced by 5 days of bile duct ligation and ethinyl estradiol administration, respectively. Bile duct ligation but not ethinyl estradiol treatments was associated with elevations of the serum bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 53 publications
4
15
1
Order By: Relevance
“…Thus, our findings do not support the concept that selective alterations in the sinusoidal surface of hepatocytes play a unique role in the pathogenesis ofEE-induced intrahepatic cholestasis (7,10). Rather, our data support, but do not yet prove, the alternative possibility that assigns the primary cause(s) of EE-induced bile secretory failure to the canalicular membrane domain of hepatocytes (2,9,46,47). Most importantly, this study indicates that a decreased canalicular ATP-dependent bile salt transport capacity is primarily responsible for the EE-induced impairment of bile salt secretion in intact liver ( 1-3, 44, 46).…”
Section: Resultscontrasting
confidence: 74%
“…Thus, our findings do not support the concept that selective alterations in the sinusoidal surface of hepatocytes play a unique role in the pathogenesis ofEE-induced intrahepatic cholestasis (7,10). Rather, our data support, but do not yet prove, the alternative possibility that assigns the primary cause(s) of EE-induced bile secretory failure to the canalicular membrane domain of hepatocytes (2,9,46,47). Most importantly, this study indicates that a decreased canalicular ATP-dependent bile salt transport capacity is primarily responsible for the EE-induced impairment of bile salt secretion in intact liver ( 1-3, 44, 46).…”
Section: Resultscontrasting
confidence: 74%
“…This fraction has been called bile salt-independent bile flow, and recent studies have demonstrated a strong correlation between hepatic Na+, K+-ATPase activity and bile flow (10), supporting the hypothesis that this component of bile flow is regulated by the sodium pump. One drug consistently shown to reduce bile salt-independent bile flow is the synthetic estrogen derivative ethinyl estradiol (17a-ethinyl-1,3,5-estratriene-3,17f3-diol) (10)(11)(12)(13).The aim of the present study was to examine whether Na+, K+-ATPase activity is reduced after ethinyl estradiol treatment and, if so, what possible mechanisms might be involved. We recently found that ethinyl estradiol significantly increases hepatic cholesterol ester concentrations by activating hepatic microsomal cholesterol acyl-CoA transferase (14).…”
mentioning
confidence: 98%
“…Liver surface membrane fractions were isolated according to Neville (17) through step 12 as described by Pohl et al (18). This surface membrane fraction is enriched in bile canalicular fronts, but also contains sinusoidal surface membranes (12,19). Microsomal fractions were prepared from the supernate of the liver surface membrane nuclear pellet by a modification of the procedure of Evans and Gurd (20) Abbreviations: ethinyl estradiol, 17a-ethinyl-1,3,5-estratriene-3,17,B-diol; ESR, electron spin resonance.…”
mentioning
confidence: 99%
See 2 more Smart Citations